Ustadz's Motivation for Islamic Boarding School Students (Interpersonal Communication Approach) - Febriansyah, Febriansyah; Kusmiati, Yopi (UIN Fatmawati Sukarno Bengkulu, 2023)
A santri should have motivation in reciting the Quran, but in a pesantren in the Ciputat area, which are supported by so many UIN Jakarta students; their interest and motivation in reciting tends to have decreased. Therefore, several external factors are needed to revive motivation in reciting Quran for santri, by providing motivation for reciting by the ustadz at the pesantren. So, in this study discusses the communication of ustadz with students, supporting factors and inhibiting motivation of students in recitung. This study uses a qualitative method with a constructivism paradigm. FIRO is used as the theory, proposed by William C, Schutz which explains one's orientation towards others. The results of the study show that the form of communication between Ustadz and Santi at Luhur sabilussalam Islamic boarding school is openness, empathy, providing support, providing teaching with a sense of humor and equality in establishing relationships. Furthermore, the form of motivation gived by ustadz with the Luhur sabilussalam Islamic boarding school students is giving gifts to students who are enthusiastic recitingQuran, telling the story of the clergy, giving praise, giving encouragement, giving an overview of future prospects. The supporting factors are the presence of an ustadz who has credibility by carrying out two-way communication, and the inhibiting factor is the lack of understanding of the character of the students, the verbalistic students are sleepy.